PELAKSANAAN DIVERSI TERHADAP ANAK YANG MENJADI PELAKU DALAM PERKARA TINDAK PIDANA KECELAKAAN LALU LINTAS (STUDI KASUS : PENETAPAN NOMOR : 223/PID.SUS-ANAK/2014/PN.BLG DI PENGADILAN NEGERI BALIGE) - Mangasitua Simanjuntak; Marlina Marlina; Mahmud Mulyadi; Edy Ikhsan (USU LAW JOURNAL, 2018)
ABSTRACT Associated with it, in the unaccommodating child protection principles particularly of non-discrimination principle that prioritizes the best interests for the child and the right to life, survival and development of the child, the legislation of the Republic of Indonesia Number 11 Year 2012 about the criminal justice system of the child which is the turn against law number 3 of the year 1997 concerning juvenile court was set up expressly concerning restorative justice and Diversion that is intended to avoid and keep children from the judicial process so that it can avoid the stigma against children who are dealing with the law and the child can go back into the social environment is reasonably. It is therefore very necessary role as well as all parties in realizing it.The concept of Versioned poured in article 7 paragraph (1) and (2) the Law Number 11 year 2012 RI about the criminal justice system requires that Children on any judicial process is initiated from the Investigator, public prosecutor or Judge has an obligation to Children implement a versioned for every child as the perpetrator of the crime of traffic accidents, based on the normative research done by acquiring legal materials of primary, secondary and tertiary diola and analyzed in perspective.That the process of implementation of the diversion is done at the stage of investigation by the investigator if not reached then the mandatory attempted diversion by the public prosecutor at the stage of prosecution and if not accomplished also then Judge in the Examination stage The matter of children in State Court seeking diversion mandatory and if that also does not reach an agreement it will be only a Matter of settlement of the child through the process of criminal justice that is closed to the public, and in the resolution of the matter of the child through the criminal justice process is still open to the unsettled versioned upon agreement of the parties: child/perpetrators, victims, parents of the victim, community counselors, and social workers Professionals based on restorative justice approaches and local wisdom Dalihan Natolu (Adat Batak Toba) who contributed positively in the achievement of a deal are versioned. Keywords             :  implementation of the Diversion, the crime of traffic accidents, local wisdom.